Tectonic-Related Geochemical and Hydrological Anomalies in Italy during the Last Fifty Years - Giovanni Martinelli; Riccardo Ciolini; Gianluca Facca; Francesco Fazio; Fabrizio Gherardi; Jens Heinicke; Lisa Pierotti (Minerals, 2021)
Seismic hazard reduction policies usually utilize earthquake catalogues and probability evaluations of occurrence. Further geophysical and geochemical parameters could contribute to hazard reduction policies as is currently the case in some countries, such as Iceland, Taiwan, China and Russian Federation. In the past four decades, intense research activity carried out by many different institutions in Italy has allowed us to recognize the most relevant sensitive sites for detecting acceleration in crustal deformation processes by means of geofluids monitoring. All scientific papers published in the period 1976–2020 concerning tectonic-related signals in geofluids have been considered. An in-depth review of previous and present-day research activities, as well as an update of two unpublished time series recorded in Central and southern Italy, has contributed to identifying areas where an instrumental array is still lacking and the most relevant priority areas for monitoring activities in geofluids. An atlas of all experimental sites utilized in recent decades has been obtained with the purpose of contributing to identifying the most suitable monitoring areas.